(untitled) (Journal of Mathematical Study, 2024)
It is well known that weak n-tilting modules are vital in tilting theory, which are generalizations of n-tilting and n-cotilting modules. The aim of this paper is to give a new characterization of weak n-tilting modules. In order to do that, we introduce the notion of weak n-star modules. We study more deeply the properties of them. Moreover, connections between (co) star and weak n-star modules are given.